Intraspecific variation of anatomical and chemical defensive traits in Maritime pine (Pinus pinaster) as factors in susceptibility to the pinewood nematode (Bursaphelenchus xylophilus) - Zas, Rafael; Moreira, Xoaquín; Ramos, Miguel; Lima, Marta R. M; Nunes da Silva, Marta; Solla, Alejandro; Vasconcelos, Marta W; Sampedro, Luis (Trees (Berlin, West), 2015)
KEY MESSAGE : Migration ability of the PWN through wood branch tissues of adult Maritime pine trees significantly differed among Iberian provenances and this variation was related to differences in anatomical and chemical defensive traits. The pinewood nematode or pine wilt nematode (PWN; Bursaphelenchus xylophilus) is one of the most dangerous threats to European coniferous forests, especially for the susceptible Maritime pine (Pinus pinaster), a valuable forest resource in South Western Europe. The PWN is vectored by beetles of the genus Monochamus (Coleoptera, Cerambycidae) and once inoculated in healthy branches, it quickly migrates downward to the main trunk through the resin canal system. Therefore, the anatomy of the resin canal system may modulate its migration and proliferation rates. Using material from nine Maritime pine Iberian provenances established in a common garden trial, we investigated whether these provenances differed in their (1) resin canal anatomy, (2) concentration of chemical defences (non-volatile resin and total polyphenolics) in stems and (3) ability of the PWN to migrate through the pine woody tissues in ‘in vitro’ bioassays. Whether variation in anatomical and chemical defensive traits relates to differences in PWN migration across populations was also investigated. Significant intraspecific variation in anatomical and chemical defensive traits and in nematode migration rates through pine tissues was observed. Moreover, the variation in nematode migration rate among pine provenances was related to differences in both anatomical and chemical features. Overall, this study highlights the role of plant genetics in the development of defensive traits against this harmful coniferous pest. The observed intraspecific variation should be taken into account when considering breeding as a strategy to provide areas of high risk of PWN with resistant genetic material.